Media Pembelajaran Berbasis Model PBL Dengan Budaya Lokal Bakpia Berbantuan Aplikasi Scratch Pada Topik Pengukuran Dan Besaran Fisika Untuk Meningkatkan Physics Identity (MAGNETON: Jurnal Inovasi Pembelajaran Fisika, 2026)
The low level of students’ physics identity remains a common issue in physics education, largely due to abstract concepts and the limited relevance of learning materials to students’ real-life experiences. This study aims to develop physics learning media based on the Problem-Based Learning (PBL) model that integrates the local culture of bakpia and utilizes the Scratch application on the topic of measurement and physical quantities to strengthen students’ physics identity. This research employed the 4D development model (Define, Design, Develop, Disseminate). The define stage included a learning needs analysis; the design stage resulted in a preliminary media framework; the develop stage produced a Scratch prototype containing bakpia cultural context, PBL scenarios, and measurement simulations; and the disseminate stage was carried out through publication. The media was validated by five validators using an assessment sheet covering content, pedagogy, technology, TPACK integration, and aesthetics and language. The validation results showed that the media achieved an overall feasibility percentage of 94.74%, categorized as very valid. The highest score was obtained in the TPACK integration aspect (98.75%), followed by content (97.5%), pedagogy (93.75%), aesthetics and language (93.3%), and technology (90%). These findings indicate that the integration of local culture, the PBL model, and Scratch technology successfully produced interactive, contextual, and meaningful learning media that have strong potential to enhance students’ physics identity. Therefore, the developed media is considered feasible for use as an alternative physics learning resource on measurement and physical quantity topics.
Keywords: Local culture; physics measurement; physics identity; problem based learning; Scratch